Multiple geochemical parameters of the Wuliying well of Beijing seismic monitoring networks probably responding to the small earthquake of Chaoyang, Beijing, in 2022 - Chen, Yuxuan; Liu, Guiping; Huang, Fuqiong; Wang, Zhiguo; Hu, Leyin; Yang, Mingbo; Sun, Xiaoru; Hua, Peixue; Zhu, Shijun; Zhang, Yanan; Wu, Xiaodong; Wang, Zhihui; et al. (Frontiers in Earth Science, 2024)
Hydrological changes in groundwater coupled with earthquakes had been documented in previous studies by global researchers. Although few reports investigate multiple geochemical parameters that respond to earthquakes, trace elements received less attention, whereas they were suggested to be more sensitive to small earthquakes than the commonly used geochemical parameters. Beijing is located in the Zhangjiakou-Bohai (Zhang-Bo) seismic belt of North China, and although the occurrence of small earthquakes is frequent, the great historic earthquake in the Sanhe-Pinggu area M8 in 1679 in the adjoining southeast of Beijing gained widespread public attention. To find effective precursors that are significant for operational earthquake forecasting of the Beijing area, we carried out a one year test research project through weekly collection of groundwater samples during June 2021 to June 2022 from the seismic monitoring well of Wuliying in northwest Beijing. The 41 trace elements chemical compositions were analyzed for each sample. During the project ongoing period, the biggest earthquake with a magnitude of ML3.3 occurred in the Chaoyang District of Beijing on 3 February 2022. The content changes in these trace elements were systematically monitored before and after the earthquake. Through retrospective research, it was found that a few sensitive trace elements were anomalous to be coupled to the earthquake, including Li, Sc, Rb, Mo, Cs, Ba, W, U, Sr, Mn, Ni, and Zn. In addition to trace elements, we examined stable isotopes of hydrogen and oxygen and the existing hydrological data on groundwater level, temperature, major ions, and gases to assess the validity of geochemistry as a monitoring and predictive tool. We only found that F- (fluorine) ions and He (helium) gas had apparent shifts related to the earthquakes, while no shifts in the groundwater level were observed. Such characteristics of multiple geochemical parameters indicate that trace elements are likely to be more sensitive to crustal strain than the groundwater level and major ions. We assumed a most likely mechanism of the combination of mixing and water–rock interactions to explain the phenomenon. The probable scenario was that minor stresses caused by the earthquakes might create micro-cracks in bedrocks, thereby leading to a small volume of chemically distinct water mixing with the original water of the aquifer, and finally, the earthquake-induced rock fractures enhance the water–rock interactions, resulting in the post-seismic recovery of trace elements and δ18O value migration to the GWML. More testing works to find other sensitive sites to investigate multiple geochemical characteristics aiming at long-term to short-term earthquake prediction in the Beijing area and Zhang-Bo seismic belt are in progress.